Analysis of Content and Relationship Dimensions of KH Ahmad Dahlan's Interpersonal Communication in Facing Conflict - Rilo Pambudi; Anang Sujoko; Reza Safitri (Universitas Darussalam Gontor, 2024)
This study discusses the analysis of KH Ahmad Dahlan's interpersonal communication and small group communication in dealing with conflict, especially as depicted in the film